Riparian Land Use and Hydrological Connectivity Influence Nutrient Retention in Tropical Rivers Receiving Wastewater Treatment Plant Discharge - Finkler, N. R.; Gücker, B.; Boëchat, I. G.; Ferreira, M. S.; Tanaka, M. O.; Cunha, D. G. F. (Frontiers in Environmental Science, 2021)
Riparian areas are recognized for their buffering capacity regarding phosphorus and nitrogen from agricultural and urban runoff. However, their role in attenuating nutrient loads transported in rivers receiving nutrient inputs from point sources (e.g., from wastewater treatment plants, WWTPs) is still little understood. Here, we investigated whether ammonium (NH4-N), nitrate (NO3-N), and soluble reactive phosphorus (SRP) retention was influenced by the riparian land use in three Brazilian rivers receiving WWTP effluents. We hypothesized that nutrient attenuation would be controlled by the hydrological connectivity between the main channel and the riparian area. We estimated retention from longitudinal patterns of dilution-corrected nutrient concentrations below the WWTPs. We explored relationships between nutrient concentrations and vegetation cover in the riparian areas (i.e., a 100-m buffer strip). We then used linear regressions between reactive (i.e., nutrients) and conservative compounds (i.e., chloride) to identify the effects of the connectivity between the rivers’ main channels and riparian areas—characterized by mixing effects causing the dilution of chloride—on nutrient concentrations. We assessed nutrient retention during periods of high (i.e., the rainy season with high water levels) and low connectivity (i.e., the dry season with low water levels). We found that increased vegetation cover along the riparian area was associated with decreased concentrations for all nutrients. Slopes of regressions between nutrients and chloride significantly differed between seasons for NO3-N (slope high = 0.38; slope low = 0.45; p = 0.003) and SRP (slope high = 1.45; slope low = 1.78; p = 0.004), suggesting effects of riparian hydrological connectivity on ambient concentrations. Slopes of NH4-N vs. chloride regressions did not differ between seasons, indicating negligible connectivity effects. During periods of high connectivity, NO3-N concentrations tended to be low relative to those of chloride (slope < 1), whereas SRP tended to be high relative to chloride (slope > 1). We attributed this difference to processes such as denitrification and riparian sediment phosphorus release. Our results highlight that seasonal connectivity between nutrient-rich river water and riparian areas could induce changes in the predominant nutrient transformation processes, thereby favoring either nutrient retention or export in such rivers.